Порванная струна: роман / Н. Александрова - Александрова Наталья (Русский проект, 2001)
Экземпляры: АБ (20171201) / Инвентарный номер: 39723 / Цена: 42.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 46 / ББК: 84(2Рос=Рус)6